The Crime Of Child Grooming As Digital Sexual Harassment In The Perspective Of Perpetrator Accountability According To Laws And Regulations In Indonesia - Zahrana Syavica; Muhammad Arif Sahlepi; Rahmayanti Rahmayanti (Utan Kayu Publishing, 2025)
The phenomenon of child grooming that develops through digital media is a form of modern sexual violence that poses a serious threat to children as a vulnerable group. This practice is carried out by the perpetrator establishing communication, building closeness, and psychological manipulation of children for the purpose of sexual exploitation. This research aims to examine the criminal act of child grooming as a form of digital sexual violence and analyze the legal accountability of perpetrators according to laws and regulations in Indonesia. The research method used is normative juridical research with a legislative and conceptual approach. The results of the study show that the crime of child grooming has been regulated in Law Number 17 of 2016 concerning Child Protection and Law Number 12 of 2022 concerning the Crime of Sexual Violence. Both regulations affirm that perpetrators can be sentenced to criminal sanctions, either in the form of imprisonment or additional penalties, taking into account the aspect of child protection as a victim. Thus, the accountability of child grooming perpetrators not only emphasizes on the criminal aspect, but also on the prevention and recovery of victims.